Geology and geochemistry of the shear-hosted Julie gold deposit, NW Ghana. (December 2015) - Amponsah, Prince Ofori; Salvi, Stefano; Béziat, Didier; Siebenaller, Luc; Baratoux, Lenka; Jessell, Mark W.
Abstract: The Leo Man Craton in West Africa is host to numerous economic gold deposits. If some regions, such as the SW of Ghana, are well known for world-class mineralizations and have been extensively studied, gold occurrences elsewhere in the craton have been discovered only in the last half a century or so, and very little is known about them. The Julie gold deposit, located in the Paleoproterozoic Birimian terrane of NW Ghana, is one such case. This deposit is hosted in a series of granitoid intrusives of TTG composition, and consists of a network of deformed, boudinaged quartz lodes (A-type veins) contained within an early DJ1 E–W trending shear zone with dextral characteristics. A conjugate set of veins (C-type) perpendicular to the A-type veins contains low grade mineralization. The main ore zone defines a lenticular corridor about 20–50 m in width and about 3.5 km along strike, trending E–W and dipping between 30 and 60°N. The corridor is strongly altered, by an assemblage of sericite + quartz + ankerite + calcite + tourmaline + pyrite. This is surrounded by a second alteration assemblage, consisting of albite + sericite + calcite + chlorite + pyrite + rutile, which marks a lateral alteration that fades into the unaltered rock. Mass balance calculations show that during alteration overall mass was conserved and elemental transfer is generally consistent with sulfidation, sericitization and carbonatization of the host TTG. Gold is closely associated with pyrite, which occurs as disseminated grains in the veins and in the host rock, within the mineralized corridor. SEM imagery and LA-ICP-MS analyses of pyrites indicate that in A-type veins gold is associated with bismuth, tellurium, lead and silver, while in C-type veins it is mostly associated with silver. Pyrites in A-type veins contain gold as inclusions and as free gold on its edges and fractures, while pyrites from C-type veins contains mostly free gold. Primary and pseudosecondary fluid inclusions from both type veins indicate circulation in the system of an aqueous-carbonic fluid of low to moderate salinity, which entered the immiscibility PT region of the H2 O–CO2 –NaCl system, at about 220 °C and <1 kbar. Highlights: One of very few published work on gold deposits in NW Ghana. Next operating mine in NW Ghana and largest deposit in this region. Relatively rare case of orogenic gold mineralization hosted in granitoids. Unusual fluid inclusion composition for orogenic gold deposits in the WAC.